Navigating the entrepreneurial landscape: Barriers encountered by students at the Innobiz DUT centre for entrepreneurship and innovation - Chitamba, Anos; Mugano, Gift; Mbona, Sizwe; Chitamba, Norman (Edelweiss Applied Science and Technology, 2025)
This study examines the obstacles faced by student entrepreneurs at the Innobiz DUT Centre for Entrepreneurship and Innovation, located at Durban University of Technology (DUT) in South Africa. Utilizing the Resource-Based View (RBV) framework, the research identifies key resource limitations—including financial, human, technological, and social factors—that significantly hinder entrepreneurial development. A quantitative survey of 76 student entrepreneurs highlights institutional and socio-economic challenges, such as restricted access to funding, mentorship, infrastructure, and networking opportunities. Additionally, psychological and academic barriers, including fear of failure and time management issues, further impede entrepreneurial participation. The findings emphasize the importance of implementing inclusive, context-specific strategies that address structural inequalities, promote experiential learning, and support student-led innovation. Recommendations include improving resource accessibility, integrating entrepreneurship education into academic programs, and strengthening institutional support systems to foster a sustainable entrepreneurial ecosystem within the university.